Driver and Barriers of ICT Adoption in Revenue Collection in Ghana: A Case of Accra Metropolitan Assembly - Fati Tahiru; Samuel Agbesi (International Telecommunications Society (ITS), 2019)
Act 462 of 1993 and Act 936 of 2016 of the Local Government of Ghana delegates power to the District and Municipal Assemblies to formulate and execute plans, programs, and strategies to effectively mobilize resources necessary for the overall development of the district and to levy and collect taxes, rates, duties, and fees. Over the years, the Accra Metropolitan Assembly (AMA) has been trying to implement what the act states. However, the Assembly faces challenges of revenue collection, storage, and dissemination of information. The main purpose of this study was to examine the drivers and barriers to ICT adoption in the operations of AMA from macro level using institutional theory and organizational factors. The study adopted inductive qualitative thematic analysis using semi-structured interviews, and document analysis. The themes that emerged from the qualitative data analysis that influence AMA ICT adoption includes top management interest and attitude, infrastructure and resources, policy directive, and organizational success. The findings also identify themes such as government directives, and contractors commission as the main barriers to ICT adoption in AMA. The study concluded by making several recommendations that includes a centralized database that will serve as a repository for property informations as well as owners details.
Keywords: 330; AMA; MIS; ICT; Revenue; Tax; Ghana